Self-Care Strategies and Barriers among Female Service Providers Working with Female Survivors of Intimate Partner Violence - Alani, Taslim; Stroink, Mirella (Canadian Journal of Counselling and Psychotherapy, 2015)
Research has made several links between work-related stress and emotional exhaustion or burnout. What have been less often explored are what strategies are used and the perceived benefits of self-care among individuals. The present study sought to better understand the perceived value of self-care and how it is employed in a sample of female service providers working with female survivors of domestic violence. Participants (n = 7) included women who work in a variety of mental health and supportive counselling roles. Data were analyzed using thematic analysis and led to the identification of 14 themes related to how well-being is affected by counsellors’ work, barriers to their self-care, and self-care strategies. Implications of the findings are included within the article.